Cost-effectiveness analysis alongside a pilot study of prophylactic negative pressure wound therapy. Issue 1 (February 2017) - Heard, Christopher; Chaboyer, Wendy; Anderson, Vinah; Gillespie, Brigid M.; Whitty, Jennifer A.
Abstract: Background: Negative pressure wound therapy (NPWT) is increasingly used prophylactically following surgery despite limited evidence of clinical or cost-effectiveness. Objective: To evaluate whether NPWT is cost-effective compared to standard care, for the prevention of surgical site infection (SSI) in obese women undergoing elective caesarean section, and inform development of a larger trial. Methods: An economic evaluation was conducted alongside a pilot randomised controlled trial at one Australian hospital, in which women were randomised to NPWT (n = 44) or standard care (n = 43). A public health care provider perspective and time horizon to four weeks post-discharge was adopted. Cost-effectiveness assessment was based on incremental cost per SSI prevented and per quality-adjusted life year (QALY) gained. Results: Patients receiving NPWT each received health care costing AU5887 (±1038) and reported 0.069 (±0.010) QALYs compared to AU5754 (±1484) and 0.066 (±0.010) QALYs for patients receiving standard care. NPWT may be slightly more costly and more effective than standard care, with estimated incremental cost-effectiveness ratios (ICERs) of AU1347 (95%CI dominant- 41, 873) per SSI prevented and AU42, 340 (95%CI dominant- 884, 019) per QALY gained. However, there was considerable uncertainty around these estimates. Conclusions: NPWT may be cost-effective in the prophylactic treatment of surgical wounds following elective caesarean section in obese women. Larger trials could clarify the cost-effectiveness of NPWT as a prophylactic treatment for SSI. Sensitive capture of QALYs and cost offsets will be important given the high level of uncertainty around the point estimate cost-effectiveness ratio which was close to conventional thresholds. Australian and New Zealand trial registration number: ACTRN12612000171819. Highlights: Cost-effectiveness study of prophylactic NPWT post caesarean section in obese women. Pilot compared costs alongside QoL and SSI incidence as outcome measures. NPWT may be cost-effective; however, results do not reach statistical significance. There is a need for larger trials to reduce uncertainty and confirm findings. Sensitive capture of QoL and cost offsets are paramount to show cost-effectiveness.